Constitutional and legal aspects of the ratio of international and domestic law - Yerzhanova, F.A.; Abdakimova, M.Yu. (Bulletin of the Karaganda University “Law Series”, 2020)
The article discusses the content and role of constitutional legal regulation of the ratio of domestic and international law in Kazakhstan and foreign countries. The authors show the domestic and foreign specifics of the constitutional regulation of the correlation of national and international law, different approaches of legislators to fixing the correlation of domestic and international law in the Basic Laws are indicated. The article also addresses the problems of interaction between international and constitutional law. The authors highlight theoretical and practical issues related to the incorporation of international law into the legal systems of states by the Constitutions of foreign countries and the Republic of Kazakhstan. Based on the comparative legal analysis, the features of fixing the correlation of domestic and international law in the constitutions of foreign countries are revealed. The issues of fixing the norms of general international law and international treaties in the Constitutions of various countries are also considered. Conclusions have been made, in particular, that the Constitution of the Republic of Kazakhstan as a whole is in line with global trends in the development of constitutional law, due to universal globalization and internationalization of law; about the need for further scientific development of theoretical and practical issues relating, for example, to the conceptand content of universally recognized principles and norms of international law, their place in the hierarchy of legal systems of states. As one of the directions for further improvement of constitutional legislation, a proposal has been formulated to include in the constitutional and legal law provisions on universally recognized principles and norms of international law on human rights.